DIMUNITION OF OCHRATOXIN A AND AFLATOXIN B1 TOXICITY ON HEMATOLOGY AND SERUM BIOCHEMISTRY OF JAPANESE QUAIL (COTURNIX JAPONICA) - M. Shahzad; M. U. R. Khan; A. Aslam; M. Younus; H. M. Khan; A. A. Anjum; S. Masood (Journal of Animal and Plant Sciences, 2014)
Toxicity of Aflatoxin B1 (AFB1) alone and in combination with Ochratoxin A (OTA) was determined in quail chicks (n=245) divided into seven groups. Feed provided to groups G1, G2 and G3 contained 1ppm OTA, 1.5ppm OTA and 2ppm OTA in combination with 1ppm AFB1, respectively.  Feed served to groups G4, G5 and G6 contained 1ppm AFB1, 1.5ppm AFB1 and 2ppm AFB1 in combination with 1ppm OTA, respectively. Feed provided to group G7 was without any toxin (control). Aspergillus flavus and Aspergillus ocharacius pure cultures were identified on the basis of colony characters and microscopic morphology. The value of AFB1 determined was 1566ppb per two gram of rice biomass and 1440ppb for OTA by HPLC. At day 14 and 21 TEC values were significantly (P<0.05) higher in control than birds reared on 1.5ppm (AFB1 and OTA) and combined toxins. Difference was more pronounced by increase in toxin level. The highest value of ESR was observed in G6 which differed significantly (P<0.05) from birds in G7 and non-significantly with birds of G2 to G5. The lowest value for packed cell volume was observed in G6 which differed significantly (P<0.05) from birds in G7. Hemoglobin concentration (Hb) of quail chicks at days 14, 21 was lowest in birds of G6 which differed significantly (P<0.05) from birds in G7.TLCwas significantly lower in groups fed on toxins than normal. The difference observed for basophile, eosinophil, lymphocyte and monocyte counts were non-significant. Serum total proteins were significantly lower in birds reared on feed having both AFB1 and OTA toxins. Serum Creatinine and Urea levels were raised significantly with higher doses of toxins. Highest values were in birds on feed with combined toxins. Presence of higher level of mycotoxins in feed of birds can change hematological and serum biochemical profiles. Birds may become prone to metabolic and non-metabolic disorders.
Keywords: Aflatoxin; Ochratoxin; Interactions; Pathology; Toxicology and Quail